Preparation method of large complex-structure high-temperature alloy casting

By adding silicon nitride coated aluminum nitride to the ceramic core composition, the problem of insufficient dimensional accuracy and strength of ceramic core in large and complex structure high-temperature alloy castings is solved, and high molding rate and low sintering shrinkage rate are achieved and high temperature strength ceramic core preparation.

CN119387500APending Publication Date: 2025-02-07AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411538832.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare large and complex structure high-temperature alloy castings with high dimensional accuracy and high strength in the prior art. The dimensional accuracy of ceramic cores directly affects the performance and safety of the entire system.

Method used

A ceramic core composition consisting of 70% to 90% by weight of quartz glass and 10% to 30% by weight of mineralizer, and 10% to 25% by weight of plasticizer and 1% to 20% by weight of nitriding are added thereto. Silicon-coated aluminum nitride to improve the dimensional accuracy and molding rate of the core.

Benefits of technology

The ceramic core molding rate prepared by this method reaches more than 99%, the sintering shrinkage rate is less than 0.05%, the room temperature strength is more than 30MPa, and the high temperature strength is more than 25MPa, which meets the high strength and dimensional accuracy requirements of large complex structure high-temperature alloy castings .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387500A_ABST
    Figure CN119387500A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a large complex-structure high-temperature alloy casting, a ceramic core used in the preparation method is prepared from a ceramic core composition, and the ceramic core composition comprises 70-90 wt% of quartz glass and 10-30 wt% of a mineralizing agent; a plasticizer accounting for 10-25 wt% of the total amount of the quartz glass and the mineralizer; and silicon nitride-coated aluminum nitride accounting for 1-20% of the total amount of the quartz glass and the mineralizing agent. The silicon nitride coated aluminum nitride is added into the composition for the ceramic core, so that the size precision of the core can be improved, and the forming rate and the strength of the core can be improved. Experimental results show that the forming rate of the ceramic core prepared from the composition for the large-size ceramic core is 99% or above, the sintering shrinkage rate is 0.3% or below, the room-temperature strength is 30 MPa or above, and the high-temperature strength is 25 MPa or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical industry, and specifically relates to a method for preparing a large-scale complex-structure high-temperature alloy casting, a composition for a ceramic core, a ceramic core and a preparation method thereof. Background Art

[0002] The ceramic core is used as a transition body to form the casting cavity. It is used to form the inner cavity structure of the casting. Together with the outer mold and the mold shell, it ensures the dimensional accuracy requirements of the casting for the cavity.

[0003] High-temperature alloys are a type of metal material that can work for a long time at high temperatures above 600°C and under certain stresses. They have excellent high-temperature strength, good oxidation resistance and thermal corrosion resistance, good fatigue performance, fracture toughness and comprehensive mechanical properties. These characteristics make high-temperature alloys widely used in aerospace, energy, chemical industry and other fields.

[0004] With the rapid development of high-tech fields such as aerospace, higher requirements are placed on the structural complexity and dimensional accuracy of high-temperature alloy castings. Large and complex high-temperature alloy castings, such as aircraft engines and ground gas turbine castings, often need to meet requirements such as high strength, high toughness, fatigue resistance, creep resistance, good dimensional stability and surface quality. As a key component in the production of high-temperature alloy castings, the dimensional accuracy of large-size ceramic cores directly affects the performance and safety of the entire system. Therefore, in the core production process, the dimensional accuracy of large-size ceramic cores must be ensured to meet the strict requirements of these high-end fields for products. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for preparing large-scale complex structure high-temperature alloy castings. The preparation method provided in this application can prepare large-size ceramic cores and large-scale complex structure high-temperature alloy castings with high dimensional accuracy and high strength.

[0006] The present application provides a composition for a large-size ceramic core, comprising: 70wt% to 90wt% of quartz glass and 10wt% to 30wt% of a mineralizer;

[0007] A plasticizer accounting for 10wt% to 25wt% of the total amount of the quartz glass and the mineralizer;

[0008] Silicon nitride coated aluminum nitride accounts for 1wt% to 20wt% of the total amount of quartz glass and mineralizer.

[0009] The present application adds aluminum nitride coated with silicon nitride to the composition for ceramic cores, which can not only improve the dimensional accuracy of the cores, but also improve the forming rate and strength of the cores.

[0010] The composition for large-size ceramic cores provided in the present application comprises 70 wt% to 90 wt% of quartz glass, preferably 75 wt% to 85 wt% of quartz glass. In some specific implementations, the particle size (D50) of the quartz glass is 50 μm to 300 μm, preferably 100 μm to 250 μm.

[0011] The composition for large-size ceramic cores provided in the present application comprises 10wt% to 30wt% of a mineralizer, preferably 15wt% to 25wt% of a mineralizer; wherein the composition comprises mullite, alumina and zircon powder in a mass ratio of 1 to 2:1 to 2:1 to 2, preferably 1:1 to 1. In some specific implementations, the particle sizes (D50) of the mullite, alumina and zircon powder are independently 20μm to 100μm, preferably 40μm to 80μm.

[0012] The composition for large-size ceramic cores provided in the present application further comprises a plasticizer accounting for 10wt% to 25wt% of the total amount of quartz glass and mineralizer, and the amount of the plasticizer is preferably 15wt% to 20wt%. In some specific implementations, the plasticizer comprises paraffin, beeswax and polyethylene in a mass ratio of 85 to 95:1 to 10:1 to 10, preferably paraffin, beeswax and polyethylene in a mass ratio of 93:5:2.

[0013] The composition for large-size ceramic cores provided in the present application also includes silicon nitride-coated aluminum nitride accounting for 1wt% to 20% of the total amount of quartz glass and mineralizer, and the amount of the silicon nitride-coated aluminum nitride is preferably 5wt% to 20wt%, and more preferably 10wt% to 15wt%. In some specific implementations, the particle size of the silicon nitride-coated aluminum nitride is 10μm to 500μm, preferably 50μm to 300μm. In some specific implementations, the silicon content in the silicon nitride-coated aluminum nitride is 10 to 500ppm, preferably 50ppm to 300ppm. The present application has no special restrictions on the source of the silicon nitride-coated aluminum nitride, and it can be prepared according to the following method:

[0014] The spherical aluminum nitride is mixed with an organic siloxane compound, ground and then heat treated in a nitrogen atmosphere to reduce and nitride the organic siloxane compound to form aluminum nitride coated with silicon nitride.

[0015] Specifically, the organosiloxane compound can be 2,4,6,8-tetramethylcyclotetrasiloxane, which is mixed with spherical aluminum nitride in a planetary grinder at a mixing temperature of 20 to 30°C for a mixing time of 5 to 15 minutes; after mixing, heat treatment is performed in a nitrogen atmosphere at a temperature of 1400 to 1500°C for a time of 2 to 5 hours, so that the organosiloxane compound is reduced and nitrided and coated on the surface of the spherical aluminum nitride. In some specific implementations, the mass ratio of the spherical aluminum nitride to the organosiloxane compound is 100:10 to 50, preferably 100:20 to 30.

[0016] The present application also provides a ceramic core, which is prepared from the composition described in the above technical solution. In some specific implementations, the maximum size of the ceramic core is 480 mm to 830 mm, preferably 500 mm to 800 mm.

[0017] The present application also provides a method for preparing a ceramic core, comprising the following steps:

[0018] The ceramic core composition described in the above technical solution is mixed and then solidified to obtain an ingot;

[0019] The ingot is crushed and then melted to obtain a liquid feed;

[0020] The liquid material is injection molded in a mold to obtain a blank;

[0021] Sintering the blank to obtain a core;

[0022] The core is strengthened to obtain a ceramic core.

[0023] The present application first mixes quartz glass, a mineralizer, a plasticizer and silicon nitride-coated aluminum nitride, and then solidifies to obtain an ingot. Specifically, the present application stirs and mixes quartz glass, a mineralizer, a plasticizer and silicon nitride-coated aluminum nitride, and the stirring speed is preferably 80r / min to 100r / min, and the stirring time is preferably more than 30h, for example, 30h to 50h. After stirring, the obtained slurry is cooled and solidified in a stainless steel plate to obtain an ingot, which should be free of impurities and uniform in color.

[0024] After obtaining the ingot, it is crushed and melted to obtain a liquid feed. Specifically, the ingot can be crushed and placed in a core pressing machine barrel for melting. In some specific implementations, the melting temperature is 100°C to 120°C, preferably 105°C to 115°C. After obtaining the liquid feed, it is kept warm and continuously stirred to prepare for subsequent injection into a mold for molding.

[0025] Before injecting the slurry into the mold, the present application first preheats the core mold. For example, the core mold can be heated to a slight heat in a heating table or oven, and then the core mold is taken out and fixed to a core pressing machine. The new mold is heated to 25°C to 40°C and kept warm at above 30°C.

[0026] After obtaining the slurry and pre-treating the core mold, start the core pressing machine for injection molding. In some specific implementations, when the top injection core pressing machine is used for injection molding, its parameters are: pressure of 1.0MPa~2.3MPa, time of 10s~30s. In some specific implementations, when the side injection press is used for injection molding, its parameters are: pressure of 2.5MPa~6.5MPa, injection time of 5s~30s, and holding time of 0s~180s. In some specific implementations, before injection molding, it is preferably also included to apply a release agent to the inner cavity of the core mold to facilitate subsequent demolding.

[0027] After injection molding, a blank is obtained, and the visually defect-free blank is hung on a hanger or placed flat in a wooden box. In some specific implementations, after the blank is obtained, it is preferably corrected, and the present application has no particular restrictions on the correction method.

[0028] After the blank is obtained, it is placed in a bowl and shaped before sintering. Specifically, a 50-60 mm thick alumina filler treated with sodium removal is filled into a clay sagger, and the blank is inserted into the filler smoothly and vertically, so that the distance between the edge of the blank and the inner surface of the bowl is 20 mm to 30 mm, and the distance between the blanks is greater than 5 mm. Then the remaining fillers are slowly poured into the sagger, and the speed should not be too fast to avoid the fillers impacting the blanks. The amount of remaining fillers used should not exceed 10% of the weight of the sagger fillers. Then the sagger is placed on a vibration table and shaped under the conditions of a vibration current of 0.5A to 1.5A and a vibration time of 10 to 30s. After the shaping is completed, sintering is performed. In some specific implementations, the furnace temperature during sintering is lower than 50°C, the heating rate of the sintering is 0.5°C / min to 2°C / min, the sintering temperature is 1100°C to 1300°C, and the sintering time is 2h to 8h.

[0029] After sintering, the surface of the obtained core is preferably ground, polished or sprayed to improve its surface finish, corrosion resistance or meet specific appearance requirements. Use professional cutting tools or equipment to cut the ceramic core into the required size and shape according to design requirements. Grind the cut ceramic core to eliminate burrs, cracks or unevenness generated during the cutting process to further improve its accuracy and surface quality. Use appropriate cleaning agents or solvents to clean the ceramic core to remove oil, dust or other impurities on the surface to ensure that it is clean and tidy. The post-processed ceramic core is fully inspected and tested, including size measurement, shape inspection, performance testing, etc., to ensure that it meets the design requirements and quality standards.

[0030] After the surface treatment is completed, the ceramic core is preferably further processed. Specifically, the processing includes:

[0031] Rough machining: Specifically, rough machining is performed on a 3-axis CNC milling machine to remove most of the excess. Set parameters such as the machine tool spindle speed and cutting feed speed to ensure a stable and efficient cutting process. During the machining process, pay attention to checking the tool wear and machining quality, and replace the tool and adjust the cutting parameters in time.

[0032] Semi-finishing: Semi-finishing is performed on the basis of rough machining to further remove the excess and improve the dimensional accuracy and surface quality of the core. Select appropriate tools and cutting parameters for processing as needed, such as using round nose tools for curved surface processing.

[0033] Finishing: Finishing is performed on a 5-axis machining center to complete the final processing of the molding surface. Parameters such as higher spindle speed and smaller cutting feed rate are set to ensure that the processing accuracy and surface finish meet the design requirements. After processing, dimensional inspection and surface quality inspection are carried out to ensure that the core meets the design requirements.

[0034] During the processing, the following methods are used to control the processing accuracy:

[0035] (1) Selection of high-precision processing equipment

[0036] (1.1) Equipment selection: Choose high-precision, high-rigidity CNC machine tools as the processing platform. Such machine tools usually have precise control systems, high-stability spindles and guide rail systems, which can ensure accuracy and stability during the processing.

[0037] (1.2) Equipment calibration: Regularly calibrate and maintain processing equipment to ensure that the accuracy of the machine tool is always maintained at the best state. This includes comprehensive inspection and adjustment of the machine tool's geometric accuracy, positioning accuracy, and repeat positioning accuracy.

[0038] (2) Optimal selection and management of cutting tools

[0039] (2.1) Tool material: According to the hardness and processing characteristics of the ceramic material, select appropriate tool materials, such as tools made of superhard materials such as diamond and cubic boron nitride (CBN). These tools have high hardness and wear resistance, and can achieve efficient and high-precision processing on ceramic materials.

[0040] (2.2) Tool management: Establish a complete tool management system, including tool selection, sharpening, inspection and replacement. Regularly inspect and sharpen the tools to ensure that the sharpness and geometric accuracy of the tools meet the processing requirements. At the same time, adjust the tool parameters in time according to the actual situation during the processing to reduce the impact of tool wear on processing accuracy.

[0041] (3) Optimization of processing parameters

[0042] (3.1) Process parameter setting: According to the physical and chemical properties of ceramic materials and the specific requirements of processing, the cutting speed, feed speed, cutting depth and other processing parameters are reasonably set. The process parameters are optimized and adjusted through experiments and simulations to obtain the best processing effect.

[0043] (3.2) Process stability control: Maintain the stability and consistency of process parameters during the processing to avoid processing errors caused by fluctuations in process parameters. This requires precise debugging and stable control of the machine tool control system to ensure the smooth progress of the processing process.

[0044] (4) Design of precision fixtures and tooling

[0045] (4.1) Fixture design: Design and select high-precision and stable fixtures and tools to fix the ceramic core. The design of fixtures and tools should fully consider the characteristics of ceramic materials and processing requirements to ensure that the position of the ceramic core is stable and not deformed during the processing.

[0046] (4.2) Tooling optimization: Optimize the design of tooling to improve processing efficiency and quality. For example, use a quick positioning device to reduce clamping time; use an auxiliary support device to increase the rigidity of the workpiece, etc.

[0047] (5) Online monitoring and compensation technology

[0048] (5.1) Online monitoring system: Introduce an online monitoring system to monitor the machining process in real time. Sensors installed on the machine tool collect data such as dimensional changes, cutting forces, etc. during the machining process in real time and analyze and process them.

[0049] (5.2) Compensation algorithm: The compensation algorithm is used to compensate and adjust the errors that occur during the processing in real time. Errors can be eliminated and processing accuracy can be improved by adjusting the control parameters of the machine tool or changing the feed path of the tool.

[0050] (6) Environmental Factor Control

[0051] (6.1) Temperature control: Ceramic materials are sensitive to temperature changes, so the temperature of the processing environment needs to be strictly controlled during the processing. Use a constant temperature processing room or temperature compensation device to keep the temperature of the processing environment stable.

[0052] (6.2) Vibration control: Vibration is one of the important factors affecting machining accuracy. Therefore, it is necessary to reduce vibration during machining and improve machining stability by optimizing the structural design of the machine tool and installing shock-absorbing devices.

[0053] After the core is processed, it is strengthened to obtain a ceramic core. The strengthening specifically includes:

[0054] The core is strengthened in a high temperature strengthener and a low temperature strengthener in sequence to obtain a ceramic core.

[0055] In some specific implementations, the high temperature strengthener includes but is not limited to ethyl silicate. Specifically, the present application steadily places the core into a high temperature strengthener such as ethyl silicate for immersion, covers the strengthening tank cover, and the immersion time is not less than 2 hours. Then take out the core and put it in the core box, place it in a ventilated place to dry, and the self-drying time is not less than 8 hours. After the self-drying is completed, put the core box containing the core into an ammonia drying box and take it out after ammonia drying for 0.5 hours to 1 hour. After ammonia drying, the core is placed in a ventilated place at room temperature for 0.5 hours, and then low-temperature strengthening is performed.

[0056] In some specific implementations, the low-temperature strengthener includes but is not limited to epoxy resin, etc. Specifically, the present application immerses the ceramic core after high-temperature strengthening into the low-temperature strengthening liquid and covers the strengthening tank cover. The cores in the strengthening tank are neatly stacked and completely immersed in the strengthening liquid, and the immersion time is not less than 1 hour. The cores are taken out of the low-temperature strengthening tank, brushed in industrial alcohol, stacked in the core box, placed in a ventilated and dry place to dry, the drying time is not less than 3 hours, and finally the cores are placed in an electric drying oven for drying and curing. A ceramic core is obtained.

[0057] In some specific implementations, the present application preferably performs quality control and testing. For example, the present application introduces online monitoring technology during the processing process to monitor the processing status and dimensional changes in real time. The data during the processing is collected and processed and analyzed by sensors and data acquisition systems to promptly discover and correct errors; or, after the processing is completed, high-precision measuring equipment (such as a three-coordinate measuring machine, a projector, etc.) is used to perform a comprehensive size and shape inspection on the core. At the same time, check whether the surface quality meets the design requirements. According to the design requirements, detailed inspection standards and acceptance specifications are formulated to ensure that the quality of the core meets the standard requirements.

[0058] The present application also provides a method for preparing a high-temperature alloy casting, which is prepared using the ceramic core described in the above technical solution or a ceramic core prepared by the method described in the above technical solution.

[0059] Specifically, the method for preparing the high temperature alloy casting comprises the following steps:

[0060] Step (i): placing the ceramic core described in the above technical solution into a wax mold of a casting to press out a wax mold, and welding the pouring system and the wax mold together to form a whole;

[0061] Step (ii): coating the entire surface of the pouring system and the wax mold after assembly and welding with ceramic slurry;

[0062] Step (iii): dewaxing the entire casting system and wax mold coated with ceramic slurry in a dewaxing kettle;

[0063] Step (iv): calcining the dewaxed pouring system and the wax mold as a whole to obtain a ceramic shell; then washing the ceramic shell with clean water, and drying the shell after washing;

[0064] Step (V): After the ceramic shell is dried, a layer of ceramic wool is coated on the pouring system position of the ceramic shell, and then the ceramic shell is placed in a vacuum induction melting furnace for preheating;

[0065] Step (six): cutting a high-temperature alloy master alloy ingot according to the weight required for casting, and placing it in a crucible in a vacuum induction melting furnace for melting;

[0066] Step (seven): pouring the molten alloy liquid into the ceramic shell; after the pouring is completed, breaking the vacuum and taking the casting out of the furnace, cutting, shell cleaning, sand blowing, and core removal are performed on the casting to obtain the casting.

[0067] In some specific implementations, in step (ii), the thickness of the ceramic slurry coated on the entire surface of the casting system and the wax mold is 5 mm to 10 mm.

[0068] In some specific implementations, in step (iii), the temperature of the dewaxing treatment is 150° C. to 200° C., and the pressure is 5 MPa to 10 MPa.

[0069] In some specific implementations, in step (iv), the calcination temperature is 900°C to 1100°C for 2h to 5h; the drying temperature is 500-800°C for 10-20min.

[0070] In some specific implementations, in step (v), the preheating temperature is 900° C. to 1200° C. and the time is 2 h to 6 h.

[0071] In some specific implementations, in step (six), the temperature of the melting treatment is 1550°C

[0072] ~1600℃, time is 20min~30min.

[0073] In some specific implementations, in step (seven), the pouring temperature is 1550° C. to 1600° C., the pouring speed is 10 kg / s to 14 kg / s, and the insulation time is 5 min to 15 min.

[0074] The composition for large-size ceramic cores provided in the present application includes: 70wt% to 90wt% of quartz glass and 10wt% to 30wt% of mineralizer; 10wt% to 25wt% of plasticizer accounting for the total amount of quartz glass and mineralizer; 1wt% to 20% of silicon nitride-coated aluminum nitride accounting for the total amount of quartz glass and mineralizer. The addition of silicon nitride-coated aluminum nitride to the composition for ceramic cores in the present application can not only improve the dimensional accuracy of the core, but also improve the forming rate and strength of the core. Experimental results show that the forming rate of the ceramic core prepared by the composition for large-size ceramic cores provided in the present application is above 99%, the sintering shrinkage is below 0.05%, the room temperature strength is above 30MPa, and the high temperature strength is above 25MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 Schematic diagram of the structure of the ceramic core prepared in the embodiment. DETAILED DESCRIPTION

[0076] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0077] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0078] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0079] The present application provides a composition for a large-size ceramic core, comprising: 70wt% to 90wt% of quartz glass and 10wt% to 30wt% of a mineralizer; 10wt% to 25wt% of a plasticizer accounting for the total amount of the quartz glass and the mineralizer; and 1wt% to 20% of silicon nitride-coated aluminum nitride accounting for the total amount of the quartz glass and the mineralizer.

[0080] The present application adds aluminum nitride coated with silicon nitride to the composition for ceramic cores, which can not only improve the dimensional accuracy of the cores, but also improve the forming rate and strength of the cores. Experimental results show that the forming rate of the ceramic cores prepared by the composition for large-size ceramic cores provided by the present application is above 99%, the sintering shrinkage is below 0.05%, the room temperature strength is above 30MPa, and the high temperature strength is above 25MPa.

[0081] The following is a detailed description of a method for preparing a large-scale complex structure high-temperature alloy casting, a ceramic core composition, a ceramic core and a preparation method thereof provided in the present application in conjunction with the embodiments.

[0082] Example 1 Preparation of Silicon Nitride Coated Aluminum Nitride Particles

[0083] 100 g of spherical aluminum nitride with a D50 particle size of 80 μm was mixed with 30 g of 2,4,6,8-tetramethylcyclotetrasiloxane, stirred and mixed at 25°C for 10 minutes in a planetary grinder, and then heated at 1450°C for 3 hours in a nitrogen atmosphere to reduce and nitride the 2,4,6,8-tetramethylcyclotetrasiloxane to form silicon nitride-coated aluminum nitride with a D50 value of 85 μm and a silicon content of 100 ppm.

[0084] Embodiments 2 to 5

[0085] The ceramic core was prepared according to the formula shown in Table 1:

[0086] Table 1 Ceramic core formula

[0087]

[0088] The D50 particle size of the quartz glass powder is 100 microns; the mineralizer is selected from mullite, alumina and zircon powder in a mass ratio of 1:1:1, the D50 particle size of the mullite is 40 μm, the D50 particle size of the alumina is 45 μm, and the D50 particle size of the zircon powder is 50 μm;

[0089] The specific preparation method is as follows:

[0090] The quartz glass powder, mineralizer, paraffin, beeswax, low-density polyethylene and silicon nitride-coated aluminum nitride were mixed and stirred at a speed of 90 r / min for 35 hours to obtain a slurry; the slurry was cooled and solidified in a stainless steel plate to obtain an ingot; the ingot was crushed and melted at 110°C in a core pressing machine barrel, and stirred for 8 hours; a 530 mm diameter annular core mold was preheated and placed on a top injection core pressing machine, heated to 30°C, and kept at 30°C for 0.5 hours; the injection pressure of the top injection core pressing machine was set to 2.0 MPa, the holding time is 20s, after spraying the release agent in the inner cavity of the core mold, the mold is closed, the nozzle of the injection machine is aligned, and the hydraulic system and automatic circulation system of the injection machine are started for injection; after the injection is completed, the mold is opened, the core is separated from the mold with an air gun, the core is taken out of the mold, and the core that is visually defect-free is hung on the hanger; alumina filler with a thickness of about 55mm and treated with sodium removal is filled in the clay sagger, and the core is inserted into the filler steadily and vertically. The distance between the edge of the core and the inner surface of the sagger is 25mm, and the core spacing is greater than 5mm. Then continue to add filler into the sagger, the added amount is 5wt% of the original filler; set the vibration table current to 1A, the vibration time to 20s, and place the sagger on the vibration table for molding; after molding, bake the sagger in a baking furnace, the furnace entry temperature is lower than 50°C, and the temperature is increased to 1200°C at a heating rate of 2°C / min, and baked for 6 hours. After baking, when the sintering furnace automatically cools down to below 350°C, open the baking furnace, and continue to cool down to below 100°C to obtain a core.

[0091] The core surface is polished, cut, ground, cleaned, and machined to obtain a circular core with a diameter of 530 mm. Figure 1 , Figure 1 Schematic diagram of the structure of the ceramic core prepared in the embodiment.

[0092] After obtaining the core, it is immersed in ethyl silicate high-temperature strengthener for 3 hours, naturally dried for 10 hours, dried in an ammonia drying oven for 1 hour, placed in ventilation at room temperature for 0.5 hours, and then immersed in low-temperature epoxy resin strengthening liquid for 2 hours. After alcohol washing, it is naturally dried for 4 hours under ventilation conditions, and dried and cured in an electric drying oven to obtain the core.

[0093] After the core is obtained, its forming rate, sintering shrinkage, room temperature strength and high temperature strength are tested. The results are shown in Table 2, which shows the performance test results of the cores prepared in the examples and comparative examples of the present application.

[0094] Comparative Example 1

[0095] The difference from Example 1 is that the silicon nitride-coated aluminum nitride prepared in Example 1 is not added, and the other steps are the same.

[0096] Comparative Example 2

[0097] The difference from Example 1 is that silicon nitride and aluminum nitride in a mass ratio of 1:10 are added to replace the silicon nitride-coated aluminum nitride prepared in Example 1, and the other steps are the same.

[0098] Example 6

[0099] The difference from Example 4 is that silicon nitride-coated aluminum nitride with a particle size of 53 μm is added, and the other steps are the same; wherein, silicon nitride-coated aluminum nitride with a particle size of 53 μm is prepared by referring to the method of Example 1, except that the particle size of the spherical aluminum nitride used as the raw material is 80 μm.

[0100] Example 7

[0101] The difference from Example 4 is that silicon nitride-coated aluminum nitride with a particle size of 210 μm is added, and the other steps are the same; wherein, silicon nitride-coated aluminum nitride with a particle size of 210 μm is prepared by referring to the method of Example 1, except that the particle size of the spherical aluminum nitride used as the raw material is 200 μm.

[0102] Table 2 Performance test results of ceramic cores prepared in Examples and Comparative Examples

[0103]

[0104] It can be seen from the above embodiments and comparative examples that adding aluminum nitride coated with silicon nitride to the core material can not only improve the dimensional accuracy of the core, but also improve the forming rate and strength of the core.

[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a large-scale complex structure high-temperature alloy casting, characterized in that: The ceramic core used is prepared from a ceramic core composition, which comprises: 70wt% to 90wt% of quartz glass and 10wt% to 30wt% of a mineralizer; A plasticizer accounting for 10wt% to 25wt% of the total amount of the quartz glass and the mineralizer; Silicon nitride coated aluminum nitride accounts for 1wt% to 20wt% of the total amount of quartz glass and mineralizer.

2. A composition for large-size ceramic cores, characterized in that: include: 70wt% to 90wt% of quartz glass and 10wt% to 30wt% of a mineralizer; A plasticizer accounting for 10wt% to 25wt% of the total amount of the quartz glass and the mineralizer; Silicon nitride coated aluminum nitride accounts for 1wt% to 20wt% of the total amount of quartz glass and mineralizer.

3. The composition for ceramic core according to claim 2, characterized in that: The particle size of the quartz glass powder is 50 μm to 300 μm; The mineralizer includes mullite, alumina and zircon powder in a mass ratio of 1-2:1-2:1-2; The polyethylene is low-density polyethylene; The plasticizer comprises paraffin, beeswax and polyethylene in a mass ratio of 85-95:1-10:1-10.

4. The composition for ceramic core according to claim 3, characterized in that The particle size of the silicon nitride-coated aluminum nitride is 10 μm to 500 μm; The silicon content in the silicon nitride-coated aluminum nitride is 10 to 500 ppm.

5. A ceramic core, characterized in that: Prepared from the composition according to any one of claims 2 to 4.

6. The ceramic core according to claim 5, characterized in that: Its maximum size is 480mm~830mm.

7. A method for preparing a ceramic core, comprising the following steps: The ceramic core composition according to claims 2 to 4 is mixed and then solidified to obtain an ingot; The ingot is crushed and then melted to obtain a liquid feed; The liquid material is injection molded in a mold to obtain a blank; Sintering the blank to obtain a core; The core is strengthened to obtain a ceramic core.

8. The preparation method according to claim 7, characterized in that: The injection molding adopts a top injection core pressing machine with a pressure of 1.0MPa to 2.3MPa and a time of 10s to 30s; The injection molding adopts a side injection molding machine, the pressure is 2.5MPa to 6.5MPa, the injection time is 5s to 30s, and the pressure holding time is 0s to 180s.

9. The preparation method according to claim 7, characterized in that: The heating rate of the sintering is 0.5°C / min to 2°C / min, the sintering temperature is 1100°C to 1300°C, and the sintering time is 2h to 8h.

10. The preparation method according to claim 7, characterized in that: The enhancements include: The core is strengthened in a high temperature strengthener and a low temperature strengthener in sequence to obtain a ceramic core.